Disparities in patient engagement with video telemedicine among high-video-use providers during the COVID-19 pandemic. Issue 4 (27th July 2021) - Grady, Connor B; Claus, Elizabeth B; Bunn, David A; Pagliaro, Jaclyn A; Lichtman, Judith H; Bhatt, Ami B
Abstract: Aims: Known racial, ethnic, age, and socioeconomic disparities in video telemedicine engagement may widen existing health inequities. We assessed if telemedicine disparities were alleviated among patients of high-video-use providers at a large cardiovascular practice. Methods and results: All telemedicine visits from 16 March to 31 October 2020 and patient demographics were collected from an administrative database. Providers in the upper quintile of video use were classified as high-video-use providers. Descriptive statistics and a multivariable logistic model were calculated to determine the distribution and predictors of a patient ever having a video visit vs. only phone visits. A total of 24 470 telemedicine visits were conducted among 18 950 patients by 169 providers. Video visits accounted for 48% of visits (52% phone). Among telemedicine visits conducted by high-video-use providers ( n  = 33), ever video patients were younger ( P < 0.001) and included 78% of Black patients vs. 86% of White patients ( P < 0.001), 74% of Hispanic patients vs. 86% of non-Hispanic patients ( P < 0.001), and 79% of public insurance patients vs. 91% of private insurance patients ( P < 0.001). High-video-use provider patients had 9.4 (95% confidence interval 8.4–10.4) times the odds of having video visit compared to low-video-use provider patients. Conclusion: These results suggest that provider-focused solutions alone, including promoting provider adoption of video visits, may not adequately reduce disparities in telemedicine engagement. Even in the presence of successful clinical infrastructure for telemedicine, individuals of Black race, Hispanic ethnicity, older age, and with public insurance continue to have decreased engagement. To achieve equity in telemedicine, patient-focused design is needed. Graphical Abstract: